Macrophage Activation and Patterns of Inflammation in Obese and Non-Obese Women with Breast Carcinoma. (January 2014) - Renne, M.; Conforti, F.; Camastra, C.; Donato, A.; Donato, G.
Tumor-associated macrophages (TAMs) with M2 phenotype provide an immunosuppressive microenvironment for tumor growth. In contrast, A great deal of evidence indicates that macrophages in obese patients' adipose tissue undergo a phenotypic change from M2 to Ml polarization accelerating adipose tissue inflammation. Interestingly, obesity is considered a major risk factor for breast cancer. Here, we report a case-control study comparing normal-weight and obese women with breast cancer. Activation states of macrophages and patterns of inflammation associated to breast invasive ductal carcinoma were analyzed by immunohistochemistry. iNOS positive macrophages were counted as a Ml polarized population. Our study demonstrates that classically activated macrophages in obese patients outnumber classically activated macrophages in the breast of non-obese patients with infiltrating ductal carcinoma. However, cancer cell linked factors may strongly antagonize Ml macrophages' positive effects by both stimulating their switching to M2 TAMs and inhibiting their effects.